Predictors of 30‐day readmissions for adrenal insufficiency: A retrospective national database study. (3rd June 2021) - Kichloo, Asim; El‐amir, Zain; Shaka, Hafeez; Wani, Farah; Syed, Sofia Junaid
Abstract: Objective: The aim of this study was to describe rates and characteristics of non‐elective 30‐day readmission among patients hospitalized for adrenal insufficiency and to assess predictors of readmission. Design: We analysed the 2018 National Readmission Database. Adrenal insufficiency hospitalizations were identified using the International Classification of Diseases, Tenth Revisions, Clinical Modification diagnosis codes for principal diagnostic codes of primary adrenal insufficiency, Addisonian crisis, drug‐induced adrenocortical insufficiency, and other and unspecified adrenocortical insufficiency. Patients: During the study period, 7738 index hospitalizations were identified as patients with AI who met the inclusion criteria. Of these, 7691 were discharged alive. Measurements: We utilized chi‐squared tests to compare baseline characteristics between readmissions and index hospitalizations. Multivariate Cox regression was used to identify independent predictors of readmission. Results: The 30‐day all‐cause readmission rate for AI was 17.3%. About 1 in 5 readmissions was for AI. Other reasons for readmission included sepsis (10.8%), unspecified pneumonia (3.1%) and acute renal failure unspecified (1.6%). Readmission was associated with significantly higher odds of inpatient mortality. Independent predictors of 30‐day all‐cause readmissions included index hospitalizations with the Charlson Comorbidity Index (CCI) ≥3 (adjusted hazards ratio (aHR): 2.53, 95% CI: 1.85–3.46, p  < .001), protein‐energy malnutrition (aHR: 1.28, 95% CI: 1.02–1.60, p  = .035) and obesity (aHR: 1.26, 95% CI: 1.02–1.56, p  = .035). Conclusions: The 30‐day all‐cause readmission rate was 17.3%. AI was the most common reason for readmission among other causes. Readmissions were associated with increased mortality. CCIs of 3 or more, protein‐energy malnutrition and obesity were significant predictors of readmission.